Dinamika AS dengan RRC Dalam Persaingan untuk Kepemimpinan Global di Bidang Artificial Intelligence tahun 2016-2019 - Ismail, Dimas Fajar Taufiq; Utomo, Tri Cahyo (Journal of International Relations, 2020)
The exponential development of the US in the field of Artificial Intelligence (AI) has given birth to various technological innovations that transforming the modern societies throughout the world and bringing the US to the top position in the current international system. However, the rapid progress of the PRC in the field of AI and its ambition to become the new global leader in this field, made the US worry that the PRC will replace the US’s position as a superpower in the international system. This study aims to analyze US and PRC policies in the competition for global leadership in the field of AI and to find out the motives that drive the US and PRC to become global leaders in this field. This study will use descriptive-qualitative design/type in order to describe and explain the actions and behaviour of US and PRC related to the competition for global leadership in the field of AI. The writer use the method of literature review for the data collection in this study. This research uses the concepts of ‘power’ and 'global leadership', then relates them to the development of science and technology. The results of this study are that the motive of accumulation of power primarily drives US and PRC policies in the competition for global leadership in the field of AI, and this competition also cause high tensions in their bilateral relations.